Sperm midpiece length predicts sperm swimming velocity in house mice - Firman, Renée C. (The Royal Society, 2010)
Evolutionary biologists have argued that there should be a positive relationship between sperm size and sperm velocity, and that these traits influence a male's sperm competitiveness. However, comparative analyses investigating the evolutionary associations between sperm competition risk and sperm morphology have reported inconsistent patterns of association, and in vitro sperm competition experiments have further confused the issue; in some species, males with longer sperm achieve more competitive fertilization, while in other species males with shorter sperm have greater sperm competitiveness. Few investigations have attempted to address this problem. Here, we investigated the relationship between sperm morphology and sperm velocity in house mice (Mus domesticus). We conducted in vitro sperm velocity assays on males from established selection lines, and found that sperm midpiece size was the only phenotypic predictor of sperm swimming velocity.